Novgorod's Political Development in 1456-1470 - Tomas Manusadžianas (Lietuvos Istorijos Studijos)
This article is the first part of a work - 'Novgorod at the political cross-roads before annexation to Moscow' (1456-1478). The work deals with a situation of Novgorod's choice of political dependence between Moscow and Lithuania during the last period of Novgorod's independence.